Podocyte GSK3 is an evolutionarily conserved critical regulator of kidney function - J. A. Hurcombe (Nature Portfolio, 2019)
Glycogen Synthase Kinase 3 (GSK3) has conserved functions across species but its role in the kidney is unclear. Here, the authors show that in the kidney podocyte cell of mice and related nephrocyte in Drosophila that GSK3 is a master regulator of function both during development and in maturity.